Management And Strategy In Waqf Institution: A Systematic Literature Review - Ramdani Ramdani; Ririn Tri Ratnasari; Imron Mawardi (Universitas Muhammadiyah Sidoarjo, 2022)
Waqf management has not been carried out optimally, waqf has not been able to play a prominent role in people's social life. Reflecting on the heyday of the Ottoman Turks, waqf was so dominant and occupied an important position. The current reality many waqf assets are unproductive and run conservatively. Therefore, this research is essential to see how waqf institutions can implement various strategies so that waqf becomes productive. The Systematic Literature Review approach explores multiple strategies by various waqf institutions. The study results show, that the strategy adopted by waqf institutions has succeeded in producing waqf assets, So waqf institutions can be more effective and efficient in carrying out their operations.